Spectrum of Diseases in the Axilla - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:This is an analysis of axillary masses to determine the spectrum of diseases that are commonly encountered in the axilla.Materials and Methods:Ten years’ consecutive analysis axillary biopsies sent to the pathology laboratory of a tertiary hospital were formalin fixed, paraffin embedded, and stained with hematoxylin and eosin (H and E). Stains such as Ziehl–Neelsen, vermentin and CD5, CD20, and CD23 were also employed in further differentiation of diseases.Results:Fifty-nine axillary lesions were analyzed from 21 males and 38 females. The ages ranged from 2 months to 80 years and peaked in the third decade of life. There were eight developmental (congenital) lesions (13.6%), seven infectious (12.0%), 12 reactive (20.3%), and 31 neoplastic lesions (52.5%). All the congenital lesions were aberrant breast tissues. There were 19 non-neoplastic lymph nodes and 12 of them (63.2%) were reactive hyperplasia remaining (35%) being granulomatous inflammations of which four were tuberculous. A case of hematoma in a 2-month-old male child was seen. The neoplastic diseases were dominated by lipoma; five cases (16.1%), non-Hodgkin’s lymphoma; 11 cases (35.5%), and metastatic carcinoma; 5 cases (16.1%).Conclusion:The most common tissue of affectation in the axilla was the lymph node. Malignant neoplastic diseases were the commonest pathology with female predisposition; the peak age of presentation was the third decade of life was the third decade. Histologic evaluation of axillary masses will aid in the prompt and appropriate treatment of diseases to reduce attendant morbidity and mortality.